RESEARCH ON INHERITANCE MECHANISM OF HENAN ZHUIZI PROVINCE, CHINA - Bie, Zhian; Photchanachan, Sarana; Bangbon, Pensri (วารสารบัณฑิตศาส์น มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2023)
Henan Zhuizi folk tradition was listed in the national intangible cultural heritage protection list in 2006 and enjoys a good reputation both at home and abroad. Nowadays, it is faced with the problem of inheriting ecological loss and inheriting people’s green and yellow, and has become an intangible cultural heritage that needs to be rescued and protected. Based on the analysis and research, it raises questions, analyzes the problems, and proposes strategies to solve the problems. Through the collection and collation of historical documents and field investigations, the system collects various kinds of materials, including audio, images, music scores, costumes, characters, inheritors, and inheritance repertoires, in the historical development stage of Henan Zhuizi, and conducts statistics and collation according to different categories. Make quantitative and qualitative analysis. Finally, an orderly mechanism for the protection and inheritance of Henan Zhuizi was constructed, and a systematic digital acquisition system, storage system and protection system were formed to effectively inherit and protect the Henan Zhuizi, so that the art of Henan Zhuizi would be carried forward. At the results of research were provide theoretical support for the construction of non-ereditary inheritance management mechanism of Henan Zhuizis,.and provide practical guidance for the protection and development of Henan Zhuizi, which embodies the prominent practical significance. With Research results have reference significance in the construction of digital platform for resource management and have academic significance in innovative thinking and new fields of multidisciplinary research methods